2018
DOI: 10.1186/s40069-018-0256-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the Surface Modification of Recycled Fine Aggregates in Aqueous H2SiF6 Solution

Abstract: Recycled aggregates (RAs) production techniques are essential for the material circulation society because RAs from demolished concrete waste can sustainably be reused as a concrete material. However, RAs can bring about several performance decreases when they are used for recycled aggregate concrete (RAC) because of the low qualities (i.e., high water-absorption rate and low density) caused by the attached hydrated cement paste on the RA surface. Therefore, both the production of high-quality RAs and the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It can be observed that the thicker and tougher of LWPA shells corresponding to the pre-soaking treated method with various ratios of w/c, which increases significantly for the TDS/0.6. According to Ryu et al [40], the improvement of compressive strength is due to the interfacial transition zone (ITZ) which is subjected to the cohesive bonding strength between the cement paste and LWA. Furthermore, the compressive strength enhancement of the concrete cube is more prominent at the latter stages due to the special impacts of the pre-soaking treated method.…”
Section: Compressive Strength Testmentioning
confidence: 99%
“…It can be observed that the thicker and tougher of LWPA shells corresponding to the pre-soaking treated method with various ratios of w/c, which increases significantly for the TDS/0.6. According to Ryu et al [40], the improvement of compressive strength is due to the interfacial transition zone (ITZ) which is subjected to the cohesive bonding strength between the cement paste and LWA. Furthermore, the compressive strength enhancement of the concrete cube is more prominent at the latter stages due to the special impacts of the pre-soaking treated method.…”
Section: Compressive Strength Testmentioning
confidence: 99%
“…Lightweight plant-based aggregate (LWPA) concrete can be categorized as a special type of concrete with a characteristic oven-dried density not more than 2000 kg/m 3 [40] Among the three types of density (DD: demoulded density, ADD: air-dry density, and ODD: oven-dry density), all specimens fell within the range of the lightweight concrete category, as presented in Figure 6. The oven-dry density and air-dry density of untreated shell mixes ranged between 1897-1908 kg/m 3 and 1973-1998 kg/m 3 , respectively.…”
Section: Densities (Demoulded Air-dry and Oven-dry)mentioning
confidence: 99%
“…The thickness and toughness of LWPA shells corresponding to the pre-soaking treatment method with various ratios of w/c increases significantly for TDS/0.6. According to Ryu et al [40], the improvement of compressive strength is due to the interfacial transition zone (ITZ), which is subjected to the cohesive bonding strength between the cement paste and LWA. Furthermore, the compressive strength enhancement of the concrete cube is more prominent at the latter stages due to the special impact of the pre-soaking treatment method.…”
Section: Mechanical Properties Of Concrete Compressive Strength Testmentioning
confidence: 99%
“…A study by Hwa-Sung Ryu [6] on "Evaluation on the Surface Modification of Recycled aggregate in aqueous H2SiF6 solution", since recycled aggregates bring about a decrease in several performances when they are used for recycled aggregate concrete (RAC) because of the low qualities caused by the attached hydrated cement paste on the RA surface. The physical properties and mechanical performance of mortars using RFA were evaluated after RFA modification.…”
Section: Literature Reviewmentioning
confidence: 99%